2006
DOI: 10.2118/89428-pa
|View full text |Cite
|
Sign up to set email alerts
|

Physically Based Capillary Pressure Correlation for Mixed-Wet Reservoirs From a Bundle-of-Tubes Model

Abstract: Summary It is shown that the main characteristics of mixed-wet capillary pressure curves with hysteretic scanning loops can be reproduced by a bundle-of-triangular-tubes model. Accurate expressions for the entry pressures are employed, truly accounting for the mixed wettability and the diverse fluid configurations that arise from contact angle hysteresis and pore shape. The simulated curves are compared with published correlations that have been suggested by inspection of laboratory data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
6
40
0
Order By: Relevance
“…In addition to predicting fundamental flow parameters (e.g., capillary pressure and relative permeability) (Kovscek et al, 1993;Øren et al, 1998;van Dijke & Sorbie, 2002a;Silin & Patzek, 2006;Helland & Skjaeveland, 2006a;Mousavi et al, 2013), pore scale modeling is also capable of investigating the effects of micro-scale phenomena on the macro-scale behaviors, and thus it provides a physically-based approach to upscale multiphase flow in porous media from micro-scale to macroscale (Middleton et al, 2012;Mehmani et al, 2012;Al-Dhahli et al, 2013;Porta et al, 2013).…”
Section: Pore Scale Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to predicting fundamental flow parameters (e.g., capillary pressure and relative permeability) (Kovscek et al, 1993;Øren et al, 1998;van Dijke & Sorbie, 2002a;Silin & Patzek, 2006;Helland & Skjaeveland, 2006a;Mousavi et al, 2013), pore scale modeling is also capable of investigating the effects of micro-scale phenomena on the macro-scale behaviors, and thus it provides a physically-based approach to upscale multiphase flow in porous media from micro-scale to macroscale (Middleton et al, 2012;Mehmani et al, 2012;Al-Dhahli et al, 2013;Porta et al, 2013).…”
Section: Pore Scale Modelingmentioning
confidence: 99%
“…Layers of oil surrounded by identical fluid (water) have a sandwiched shape and can exist at negative capillary pressure during forced imbibition in mixed-wet pore spaces (Kovscek et al, 1993;Blunt, 1997b;Piri & Blunt, 2004;Helland & Skjaeveland, 2006a; as shown in Figure 2.3(a). However, this sandwiched shape layer type can also occur in pore necks during primary drainage process , in which water is the layer fluid surrounded by oil, see Layers surrounded by different fluids are formed by intermediate-wet…”
Section: Layer Typementioning
confidence: 99%
See 3 more Smart Citations